Effect of VMBR Training on Psychological Dimensions of Anxiety and Mental Toughness of Table Tennis Players - Sharma, Arnav; Prasad, Brij Kishore (Physical Education Theory and Methodology, 2023)
Study purpose. The study was conducted to examine the effects of Visual Motor Behavior Rehearsal (VMBR) Training on sports anxiety and mental toughness of table tennis players after six weeks of the training. Materials and methods. Fifty male state-level table tennis players within the age group of 17 to 23 years were selected from Inspire Table Tennis Academy, Secunderabad, Telangana and divided randomly into two groups, the Control and Main Groups, each one consisting of 25 subjects. The Main Group underwent VMBR Training for six weeks, three times a week, and the Control Group was not involved in any kind of training program except for their daily practice. Measurements of anxiety of all table tennis players with the use of Sports Anxiety Scale-2 (SAS-2) with three dimensions which were somatic, worry and concentration disruption developed by Ronald E. Smith, Frank L. Smoll, Sean P. Cumming, and Joel R. Grossbard in 2006 and Sports Mental Toughness Questionnaire (SMTQ) with three dimensions which were confidence, consistency and control developed by Michael Sheard, Jim Golby, and Anna Van Wersch in 2009 were taken at the beginning of and after the experimental period of six weeks. Results. Significant effect was found in the Main Group at a significance level of 0.05 for dimensions which were sports mental toughness and somatic, worry and concentration disruption from anxiety scale dimensions of table tennis players. Conclusions. The visualization and imagery has been used as an effective tool for enhancing performance. Visual-Motor Behavior Rehearsal is a systematic psychological technique that helps table tennis players in overcoming psychological factors.